Contribution of moral Sufism learning to Adversity Quotient - Fatimah Munawaroh (ATTARBIYAH: Journal of Islamic Culture and Education, 2018)
Various problems possessed by students often become stressors and symptoms of spiritual diseases. Therefore, it is necessary to resolve these issues using teaching of Sufism. This study aims to know morals education practice of Sufism and Adversity Quotient (AQ) of IAIN Salatiga students as well as contributions of learning behavior against Mysticism Adversity Quotient. This type of research is qualitative; the techniques of collecting data are interviews, observation, and documentation. Results from this study showed that, first, learning morals Sufism at IAIN Salatiga including the category of learning that meets the learning component morals mysticism, of which approach direct experience using project methods, equipped with media and learning resources that are relevant, motivating students to develop ma'rifatullah potential and has a purpose. Second, intelligence adversity of the students showed high category. This is evidenced by the high average score of students in the assessment of appropriate attitudes and behavior indicators AQ. Third, the moralteaching of Sufism contributed to the adversity quotient of IAIN Salatiga students evidenced by the formation of attitudes and behavior optimistic, confident, capable heartened, able to withstand reproach, aspire big,accept criticism and able to hit the target.